INFLUENCE OF AUDIO MEDIA ON DENTAL HEALTH KNOWLEDGE OF VISUALLY IMPAIRED STUDENTS AT SLB-A JAKARTA INDONESIA - Sulistiani, Silvia; Ulliana; Sahana Vanka, Karra (Journal of Health and Dental Sciences, 2025)
Oral health is an integral part of overall health. Children with special needs, including the visually impaired, require appropriate information media to improve their knowledge of oral and dental health. This study aims to assess the effectiveness of audio-based counselling for visually impaired children. The method was quasi-experimental study used a pre-test and post-test design on 67 visually impaired students at SLB-A Pembina Tingkat Nasional Jakarta, selected through total sampling. Dental and oral health education was delivered via audio media, and knowledge was assessed using Braille-format questionnaires. Responses were recorded by the researcher. Inclusion criteria included adequate hearing, cognitive ability, and consent, while exclusions were similar ongoing studies, hearing impairment, additional disabilities, or communication difficulties. Data were analyzed with SPSS using normality tests, followed by the Wilcoxon test due to non-normal distribution. The results show that audio media is effective in increasing knowledge of oral and dental health, with ρ=0.000 (ρ<0.05), although other research factors did not have a significant effect. Conclusion: Audio media effectively improves dental and oral health knowledge of visually impaired students, independent of demographic factors, with strong support from parents and schools. DOI : 10.54052/jhds.v5n2.p127-140